Bisulfone‐Functionalized Organic Polymer Photocatalysts for High‐Performance Hydrogen Evolution. Issue 2 (16th December 2019) - Shu, Chang; Zhao, Yongbo; Zhang, Chong; Gao, Xiaomin; Ma, Wenyan; Ren, Shi‐Bin; Wang, Feng; Chen, Yu; Zeng, Jing Hui; Jiang, Jia‐Xing
Abstract: Conjugated polymers show great potential in the application of photocatalysis, particularly for the photoreduction reaction of water to generate hydrogen. Molecular structure design is a key part for building a high‐performance organic photocatalyst. Herein, two bisulfone‐containing conjugated polymer photocatalysts were constructed with 1D or 3D polymer structures, and the effect of polymer geometry on photocatalytic activity was studied. It was found that the linear polymer PySEO‐1 exhibited increased photocatalytic performance compared with the 3D polymer network PySEO‐2 because the enhanced coplanarity of the polymeric chain in PySEO‐1 promoted the photogenerated charge‐carrier transmission along the 1D main chain. As a result, an attractive hydrogen generation rate of 9477 μmol h −1 g −1 was obtained with PySEO‐1 under broadband light irradiation. PySEO‐1 also exhibited a high external quantum efficiency of 4.1 % at an incident light wavelength of 400 nm, demonstrating that the bisulfone‐containing polymers are attractive as organic photocatalysts for hydrogen production. Abstract : Polymers for photocatalysis : Bisulfone‐containing conjugated polymer photocatalysts with 1D and 3D structures are developed. The linear polymer exhibits an attractive hydrogen generation rate of 9477 μmol h −1 g −1 under UV/Vis light irradiation.